Studento žinių sisteminimas taikomosios matematikos kurse - Šileikienė, Regina Dalytė; Lukoševičiūtė, Kristina (Lietuvos matematikos rinkinys, 2021)
The methodology for the systematization of the student’s knowledge was discussed. The student when solving some mathematical problem has to return to theoreticalmodels from time to time, to analyze them,  to compare them to the solutions made by computer and to describe the suitability of the methodology.